Let’s Learn Foreign Languages with Computers - Ramoškiene, Aldona; Šernas, Vytautas (Acta Paedagogica Vilnensia, 2000)
One of the fundamental tasks for Lithuania is to modernize its education system. People of Lithuania have to be educated and trained to use up-to-date information technology to be able to compete on global markets. The only way to do this is to teach information technology at school. Computers have been used in Lithuanian schools since 1985, when information science was made a mandatory subject. But there was no uniform policy of supplying schools with computers. Only when the Information and Forecasting Centre (IFC) was established in 1990 mostly IBM Computers were purchased in a centralised manner mainly from the funds of municipalities and private funds. The Open Society Foundation of Lithuania also contributed and later in 1996 this Fund made a very great contribution into computerization of all the Lithuanian secondary schools. The article is mostly devoted to the problems of foreign language teaching using computers. One of the authors of this article took part in workshop No. 2/96 (20-24 February, 1996) “Computers in the Foreign Language Classroom”, at the European Centre for Modern Languages, Graz, Austria and presents some methodological and pedagogical ideas concerning the use of computers in a foreign language classroom.